Scanning tunnelling spectroscopy and manipulation of double-decker phthalocyanine molecules on a semiconductor surface. (7th August 2017) - Pan, Yi; Kanisawa, Kiyoshi; Ishikawa, Naoto; Fölsch, Stefan
Abstract: A scanning tunnelling microscope (STM) operated at 5 K was used to study dysprosium biphthalocyanine (DyPc2 ) molecules adsorbed on the inert III–V semiconductor surface InAs(1 1 1)A. Orbital imaging and scanning tunnelling spectroscopy measurements reveal that the molecular electronic structure remains largely unperturbed, indicating a weak molecule-surface binding. The molecule adsorbs at the In vacancy site of the (2  ×  2)-reconstructed surface and is highly sensitive to current-induced excitations leading to random rotational fluctuations. Owing to the weak surface binding, individual molecules can be precisely repositioned and arranged by the STM tip via attractive tip-molecule interaction. In this way, DyPc2 dimers of well-defined internal structure can be assembled which exist in two conformations of equivalent appearance. A binary switching between these two conformers can be induced by injecting electrons into one of the two molecules. The conformational change of the dimer proceeds via a concerted molecular rotation and minor lateral displacement. The synchronised switching observed here is attributed to steric interactions between the two molecules constituting the dimer.